Ambition, a history : from vice to virtue - King, Casey (William Casey) (Yale University Press, 2013)
Is "ambitious" a compliment' It depends: "[A] masterpiece of intellectual and cultural history."'David Brion Davis, author of Inhuman Bondage: The Rise and Fall of Slavery in the New World From rags to riches, log house to White House, enslaved to liberator, ghetto to CEO, ambition fuels the American Dream. Yet at the time of the nation's founding, ambition was viewed as a dangerous vice, everything from "a canker on the soul" to the impetus for original sin. This engaging book explores ambition's surprising transformation, tracing attitudes from classical antiquity to early modern Europe to the New World and America's founding. From this broad historical perspective, William Casey King deepens our understanding of the American mythos and offers a striking reinterpretation of the introduction to the Declaration of Independence. Through an innovative array of sources and authors'Aquinas, Dante, Machiavelli, the Geneva Bible, Marlowe, Shakespeare, Thomas Jefferson, and many others'King demonstrates that a transformed view of ambition became possible the moment Europe realized that Columbus had discovered not a new route but a new world. In addition the author argues that reconstituting ambition as a virtue was a necessary precondition of the American republic. The book suggests that even in the twenty-first century, ambition has never fully lost its ties to vice and continues to exhibit a dual nature'positive or negative depending upon the ends, the means, and the individual involved